Determinants for Positioning and Promoting TVET in Tanzania: Information for Developing a Marketing Strategy - Mulongo, Godfrey; Kitururu, Issack; Irira, & Moses (Journal of Technical Education and Training, 2016)
This paper highlights important determinants for positioning and promoting TVET programs in Tanzania. The paper provides information that could provide operational insight to support the development of a marketing strategy and tools to promote TVET programs. While conducting this study, we reviewed literature to gain a better understanding of the situation of TVET in Tanzania. The findings from the literature review are complemented by a qualitative field study that analyses the factors, challenges and determinants for positioning and marketing of TVET in Tanzania.